Cooling of highly-charged, short-lived ions for precision mass spectrometry at TRIUMF's Ion Trap for Atomic and Nuclear Science - Schultz, Brad; Chowdhury, U.; Simon, Vanessa Véronique; Andreoiu, C.; Chaudhuri, A.; Gallant, A. T.; Kwiatkowski, A. A.; Macdonald, T. D.; Simon, M. C.; Dilling, J.; Gwinner, G. (Physica scripta, 2013)
At TRIUMF's Ion Trap for Atomic and Nuclear Science (TITAN), masses of short-lived nuclides are measured accurately and precisely using Penning trap mass spectrometry. The achievable precision is primarily limited by the radioactive lifetime of the nuclides. To boost the precision TITAN has demonstrated that short-lived isotopes can be charge-bred to higher charge states within 10-100 s of ms using an electron beam ion trap. The charge breeding process increases the energy spread of the ions, which in turn affects the precision and the efficiency. A novel cooler Penning trap (CPET) has been developed to trap and cool highly-charged ions using electrons prior to the precision measurement. A discussion of electron cooling and the current status of CPET will be given.
Gesehen am 26.07.2021